Sustainable Operations Management : Advances in Strategy and Methodology - Chiarini, Andrea(ed.) (New York Springer, 2015)
This book presents innovative research on various aspects of sustainability in the field of operations management and illustrates the potential of sustainability thinking and practice to improve operations performance and thereby meet customer needs. Particular attention is devoted to corporate social responsibility and marketing strategy, knowledge management for sustainability, the role of culture in a sustainable built environment, sustainable manufacturing through the application of lean and green concepts, advancing sustainability through ISO standards, and the sustainable supply chain. The present decade is proving to be a time of change in terms of business strategies and operations management. Many of the trends are still subject to uncertainty, but an understanding of the need for, and benefits of, sustainability can give a clear indication of their trajectory. Consumers and markets in general believe that while implementing their business strategies, companies should also try to improve society and the environment and to exercise social responsibility toward their employees. This book provides insights into how this may be achieved, and it is recommended for researchers as well as all practitioners and managers dedicated to enhancing sustainability in operations.
Keywords: Business ethics; Decision making; Leadership; Operations research; Organization; Planning; Production management; Sustainable development; Operations Research/Decision Theory; Business Ethics; Business Strategy/Leadership.; Operations Management; Organization; Sustainable Development